PENGARUH PENGGUNAAN GAWAI MELALUI GAMIFIKASI TERHADAP MOTIVASI BELAJAR SISWA MANAJEMEN PERKANTORAN SMK NEGERI 48 JAKARTA - Jofarhan Muhammad; Henry Eryanto; Ria Rahma Nida (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the effect of gadget use on learning motivation through gamification among Office Management students at SMK Negeri 48 Jakarta. The study employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to Office Management students at SMK Negeri 48 Jakarta and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the SmartPLS 4 software. The variables examined consisted of gadget use as the independent variable, gamification as the intervening variable, and learning motivation as the dependent variable. The results revealed that gadget use had a positive and significant effect on gamification, with a path coefficient of 0.785 and a p-value of 0.000 (< 0.05). Gadget use also had a positive and significant effect on learning motivation, with a path coefficient of 0.557 and a p-value of 0.000 (< 0.05). Furthermore, gamification had a positive and significant effect on learning motivation, with a path coefficient of 0.430 and a p-value of 0.000 (< 0.05). The findings also demonstrated that gamification positively and significantly mediated the effect of gadget use on learning motivation. Based on these findings, it can be concluded that the effective use of gadgets supported by gamification can enhance students' learning motivation. Therefore, teachers are encouraged to optimize the use of gadgets through gamification-based learning strategies to create a more interactive, engaging, and motivating learning environment.